2019
DOI: 10.1007/s11418-019-01283-x
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the possible anti-tumor effect of yokukansan

Abstract: The Kampo medicine Yokukansan (YKS) has a wide variety of properties such as anxiolytic, anti-inflammatory and analgesic effects, and is also thought to regulate tumor suppression. In this study, we investigated the anti-tumor effect of YKS. We used Lewis lung carcinoma (LLC)-bearing mice that were fed food pellets containing YKS and then performed a fecal microbiota analysis, a microarray analysis for microRNAs (miRNAs) and an in vitro anti-tumor assay. The fecal microbiota analysis revealed that treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Hub genes and their corresponded target miRNAs are presented in Table . Finally, 31 miRNAs, whose functions were correlated with tumor progression (Chang et al, ; Chang et al, ; Chen et al, ; Gao et al, ; Gu et al, ; Han et al, ; He et al, ; Kucuksayan et al, ; Li, Ma, Zhang, Ji, & Jin, ; Li, Ran, et al, ; Li & He, ; Li, Fu, et al, ; Li, Cui, Li, Zhang, & Li, ; Liu et al, ; Liu, Liu, Deng, et al, ; Liu, Liu, & Lu, ; Liu, Liu, Zhang, Tong, & Gan, ; Liu, Miao, et al, ; Luo et al, ; Tang et al, ; Wang et al, ; Wang, Cao, Su, Li, & Yan, ; Wu et al, ; Wu, Mo, Wan, Dan, & Hu, ; Xia, Jing, Li, & Lv, ; Xu et al, ; Zeng et al, ; Zhang, Hao, et al, ; Zhang et al, , ; Zhu et al, ), drug resistance (Bian et al, ; Gao et al, ; Lin, Xie, Lu, Hu, & Chang, ; Pan, Chen, Shen, & Tantai, ; Su et al, ; Xu et al, ; Zhou, Wang, & Feng, ), radiosensitivity (Liu, Li, & Gao, ), recurrence (Sim et al, ) or autophagy (Pan et al, ) in lung cancer, were identified (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Hub genes and their corresponded target miRNAs are presented in Table . Finally, 31 miRNAs, whose functions were correlated with tumor progression (Chang et al, ; Chang et al, ; Chen et al, ; Gao et al, ; Gu et al, ; Han et al, ; He et al, ; Kucuksayan et al, ; Li, Ma, Zhang, Ji, & Jin, ; Li, Ran, et al, ; Li & He, ; Li, Fu, et al, ; Li, Cui, Li, Zhang, & Li, ; Liu et al, ; Liu, Liu, Deng, et al, ; Liu, Liu, & Lu, ; Liu, Liu, Zhang, Tong, & Gan, ; Liu, Miao, et al, ; Luo et al, ; Tang et al, ; Wang et al, ; Wang, Cao, Su, Li, & Yan, ; Wu et al, ; Wu, Mo, Wan, Dan, & Hu, ; Xia, Jing, Li, & Lv, ; Xu et al, ; Zeng et al, ; Zhang, Hao, et al, ; Zhang et al, , ; Zhu et al, ), drug resistance (Bian et al, ; Gao et al, ; Lin, Xie, Lu, Hu, & Chang, ; Pan, Chen, Shen, & Tantai, ; Su et al, ; Xu et al, ; Zhou, Wang, & Feng, ), radiosensitivity (Liu, Li, & Gao, ), recurrence (Sim et al, ) or autophagy (Pan et al, ) in lung cancer, were identified (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer incidence and mortality in 2018 worldwide (Bray et al, 2018). Yokukansan, a traditional Chinese medicine (TCM) formula consisting of seven herbs (Table 2), exerted anti-tumor effects in Lewis lung carcinoma-bearing C57BL/6 mice, enriching bacteria belonging to the order Bacteroidales and family Desulfovibrionaceae (Han et al, 2019).…”
Section: Lung Cancermentioning
confidence: 99%
“…The supporting information can be downloaded at: . References [ 345 , 346 , 347 , 348 , 349 , 350 ] are cited in the Supplementary Materials .…”
mentioning
confidence: 99%